COMPARATIVE STUDY OF CAPRINE BRUCELLOSIS AND ZOONOTIC THREATS AT TWO SANITARY SECTORS OF BISKRA GOVERNORATE, ALGERIA - Adel Mammeri (Agricultura)
Brucellosis is considered as a zoonosis with a great impact in rural regions of Algeria. The consumption of raw goat milk is one of the major risk factors for brucellosis. A comparative serological study of caprine brucellosis was conducted in the area of the municipalities belonging to the sanitary sectors (S.S) of Biskra and Ouled Djellal, using the Rose Bengal test (R.B.T) (SPINREACT, Spain). A total of 789 blood samples from adult goats were analyzed, among 19 flocks, with a total population of 2065 sheep and goats. It resulted that the apparent prevalence (Pa) of brucellosis is 3.21% within the S.S of Biskra, while it is 16.15% within the S.S of Ouled Djellal. This difference between the two S.S was found to be significant via Chi-square test (p < 0.05).68.48% of total herds sampled in the whole study area were infected. 47.36% of the herds present an infection rate higher than 5%, versus 52.63% with an infection rate lower than 5%. At the level of the S.S of Biskra, 50% of the visited herds were positive to R.B.T, and 30% of the herds show an infection rate higher than 5%. However, at the level of the S.S of Ouled Djellal, 88.9 % of the sampled herds were positive to R.B.T, and 66.7 % of the herds present an infection rate higher than 5 %. It could be concluded that the high density of small ruminants, contributes to the persistence of brucellosis in the pastoral regions of the study area.